Fundacje prawa publicznego – charakterystyka na przykładzie fundacji Zakłady Kórnickie - Sobczak, Agnieszka (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostęne wyłącznie w języku angielskim: A legal analysis of the public law foundation, a type of third sector entity separately regulated by Polish legislation. An article discussing the public law foundation construct with private foundations and explains the workings of the relevant legal mechanisms, illustrating her remarks with concrete example – foundation Zakłady Kórnickie.